Referenciais freireanos para o ensino da leitura: um estudo de caso no município de Diadema - São Paulo - Fantini, Elenir Aparecida (2009)
This dissertation is intended to verify and analyze the influence of Paulo Freire thoughts in reading taught on the Diadema City, São Paulo, educational politics. This work integrates a wider research, developed by the Paulo Freire Chair on the Pontifical Catholic University of São Paulo, coordinated by Ana Maria Saul teacher, carried through the national territory to investigate The Paulo Freire presence on Brazilian Education: educational public system analysis, from the 90th decade. Specifically, this research is intended to investigate how the freirean principles materialize on the teachers, who teach reading, formation and practice. The theoretical referencial which has oriented this research data collection and analysis is constituted by principles and concepts which integrate the Paulo Freire educational proposal. It s treated as a case study inserted in a qualitative research methodology. For the investigation development, the following procedures are used for evidence collection: documents analysis, field observing and halfstructured interviews. The results analysis demonstrated that the freirean concepts are guidelines for reading taught on the researched school. It was able to conclude, from the observations and interviews, the importance that the educators put on reading, in a school building process in which educators value critic education and are available to dialogue